Asymptotic Covariance Matrices of Two-Stage Probit and Two-Stage Tobit Methods for Simultaneous Equations Models with Selectivity - Lee, Lung-Fei; Maddala, G. S.; Trost, R. P. (Econometrica, 1980)
Lung-Fei Lee, G. S. Maddala, R. P. Trost, Asymptotic Covariance Matrices of Two-Stage Probit and Two-Stage Tobit Methods for Simultaneous Equations Models with Selectivity, Econometrica, Vol. 48, No. 2 (Mar., 1980), pp. 491-503